Efficient synthesis of functionalized 2-iminothiazolines by ultrasonication under solvent-free conditions and access to 5-aryl-2-iminothiazolines - Chandan Bodhak; Subhro Mandal; Pia Dey; Samir Kumar Mukherjee; Animesh Pramanik (Results in Chemistry, 2022)
An ultrasound assisted methodology has been developed for rapid synthesis of a series of biologically important 2-iminothiazolines from easily available α-bromoketones and thioureas under solvent- and catalyst-free conditions at room temperature in open air. The 2-iminothiazolines are found to exhibit moderate activity against both the representative Gram positive and Gram negative bacteria, suggesting possible scope of using them as antimicrobials. Additionally Suzuki cross-coupling of 5-bromo-2-iminothiazolines with organoboronic acids produced fully substituted 5-aryl-2-iminothiazolines in good yield.